Transparency Of Information In Upselling Practices In The Modern Retail Industry - Aurellia Zerikha Syah; Heru Sugiyono (Fakultas Syariah INSURI Ponorogo, 2025)
The development of globalization and digital technology has spurred the evolution of selling practices in modern retail and e-commerce, which, lacking information transparency, can harm consumers via dark patterns. This study aims to analyze the role and responsibilities of the National Consumer Protection Agency (BPKN) in addressing upselling in Indonesia and compare its enforcement with the Federal Trade Commission (FTC) in the United States. The methodology employed is normative juridical, complemented by primary empirical data from interviews with BPKN and YLKI, using a comparative approach. Findings indicate that BPKN is passive and reactive, limited to a recommendatory function, which hinders optimal consumer protection. In sharp contrast, the FTC adopts a conduct-based model with strict investigative and punitive authority, imposing substantial sanctions to combat deceptive digital practices. The low transparency in Indonesia is attributed to the general regulatory framework (UUPK) and BPKN's institutional limitations. This study concludes that strengthening technical regulations, promoting proactive monitoring, and increasing BPKN's authority are essential for creating more adaptive and effective consumer protection.